The impact of weight change on suicide mortality: a nationwide population-based cohort study of 2 million Koreans - Kyuho Kim; Jin-Hyung Jung; Yoo Hyun Um; Yu-Bae Ahn; Seung-Hyun Ko; Kyungdo Han; Jae-Seung Yun (Diabetology & Metabolic Syndrome)
Abstract Background Previous studies have shown that weight change has a reverse J-shape association with all-cause mortality. However, its association with suicide mortality remains undetermined. In this study, we investigated the association between weight change and suicide mortality using a large-scale, population-based cohort from the Korean National Health Insurance Service database. Methods A total of 2,103,525 subjects aged ≥ 20 years who underwent a general health screening program twice in the 2-year interval between 2007 and 2009 were included. Subjects were categorized into five groups according to the percent weight change during this period: severe weight loss (< − 15.0%), moderate weight loss (− 15.0 to < − 5.0%), weight stable (− 5.0 to < 5.0%), moderate weight gain (5.0 to < 15.0%), and severe weight gain (≥ 15.0%). Results During a median follow-up of 11.3 years, 6,179 cases (0.3%) of suicide mortality occurred. Weight change was associated with increased suicide mortality in a reverse J-shaped curve, even after adjustment for covariates. In particular, those with severe weight loss or gain showed 1.8-fold or 1.6-fold increased risk of suicide mortality, respectively. This reverse J-shaped association was consistently observed in subgroup analyses considering age, sex, depression, cancer, and BMI category. Conclusions Moderate to severe weight change within a 2-year interval is associated with increased risk of suicide mortality. To better understand the mechanisms through which weight change affects suicide mortality, studies incorporating information on weight change intentions, medications, weight change-related medical conditions are needed.